Setting up an integrated pest management network for the Caribbean II - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Based on an analysis of the national IPM programmes in 12 Caribbean countries, workshop participants discussed the objectives of a Caribbean IPM network involving government institutions, NGOs, universities and research centres.